Cesarean Sections for High-Risk Births: Health, Fertility and Labor Market Outcomes - Hanna Mühlrad (Lund University, School of Economics and Management, Department of Economics, 2018)
Despite the fact that Cesarean section (C-section) is the most commonly performed surgery in a number of industrialized countries, little is known about the long-term consequences for the mothers and children involved. In this study, I use a sample of high-risk births—namely, breech births, in which the fetus is presented with its head upward instead of downward—to study the causal effect of C-sections on child health and on the health, fertility and labor market responses for mothers. Because selection into C-section may be endogenous, I exploit an information shock to doctors in 2000, in which new scientific evidence about the benefits of planned C-sections for breech births led to a sharp 23% increase in planned C-sections. Using Swedish registry data, I find that having a C-section improves child health in both the short and long run, indicated by higher Apgar scores at birth and fewer nights hospitalized during ages 1-7. I find little evidence to suggest any significant impact on maternal health, future fertility or maternal labor market outcomes.
Keywords: I11; I12; I38; J13; J24; 330; Cesarean Section; Fertility; Maternal Health; Child Health; Birth Technology; Labor Market Outcomes